PENGEMBANGAN MODUL BIMBINGAN PRIBADI SOSIAL BAGI GURU BIMBINGAN KONSELING UNTUK MENGHADAPI BENCANA ALAM - Ayriza, Yulia (Jurnal Kependidikan, 2009)
This study was aimed at developing module material for Guidance and Counseling teachers to increase the psychological preparedness of senior high school students in facing natural disasters. Using the research and development approach, the researcher involved 48 Guidance and Counseling teachers in the special region of Yogyakarta as research participants for needs assessment purposes. The modules were tried out to Guidance and Counseling teachers of senior high schools in the special region of Yogyakarta, involving 6 people at the initial field, 15 people at the main field, and 65 people at the operational field. Instruments applied to collect data were either opened or closed questionnaires. The collected data, the quantitative as well as the qualitative ones, were analyzed descriptively. Results obtained from this study are: (1) Material required by Guidance and Counseling teachers for module of psychological preparedness in facing natural disaster cover cognitive aspects ( 14,58%), affective aspects ( 31,25%) and psychomotoric aspects ( 52,08%); (2) The module of "Personal-Sosial Guidance for increasing Psychological Preparedness of Students in Facing Natural Disasters" cover three activities of personal-sosial services, each to face natural disasters of (a) earthquake, (b) mount eruption, and (c) tropical cyclone; and (3) The module validated is valued proper either in appearance or in concept, and is also useful as media for assisting to perform service of personal-sosial guidance to increase psychological preparedness of senior high school students in facing natural disaster. Further, the module is valued as self-contained for having fulfilled acceptance criterion (subjects reaching 80% of minimum understanding) at the test of content understanding and module readability.